2004
DOI: 10.1111/j.1756-1051.2004.tb01938.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine epibenthic dinoflagellates from Malaysia‐a study of live cultures and preserved samples based on light and scanning electron microscopy

Abstract: Marine epibenthic dinoflagellates have been collected from macroalgae, dead corals, seagrasses and sand in Malaysia and identified using light microscopy, including epifluorescence microscopy, and scanning electron microscopy. Examination of 62 samples revealed that Malaysia has rich diversity of benthic dinoflagellates, with 24 species representing 9 genera. Of these species, 8 were shown to be potentially toxic using the Anemia bioassay test i.e. Prorocentrum arenarium, P. lima, P. concavum, P. cf. faustiae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 78 publications
9
72
1
9
Order By: Relevance
“…The smallest and roundest (L/W 1.18) strain is Dn31EHU, the one that more closely matches the dimensions of the original description of P. emarginatum (Fukuyo, 1981), which was described as being 35-36 mm long and 32 mm wide (L/W 1.11). It also matches the description of P. emarginatum from the western Indian Ocean (Hansen et al, 2001), from Greek waters (Aligizaki et al, 2009) and from Malaysia (Mohammad-Noor et al, 2006), although a pyrenoid was observed in some cells in the latter two studies. The most elongated strain is Dn32EHU (L/W 1.38), which shows a thecal surface with scarce pores without a clear radiating pattern.…”
Section: Taxonomic Remarkssupporting
confidence: 63%
See 4 more Smart Citations
“…The smallest and roundest (L/W 1.18) strain is Dn31EHU, the one that more closely matches the dimensions of the original description of P. emarginatum (Fukuyo, 1981), which was described as being 35-36 mm long and 32 mm wide (L/W 1.11). It also matches the description of P. emarginatum from the western Indian Ocean (Hansen et al, 2001), from Greek waters (Aligizaki et al, 2009) and from Malaysia (Mohammad-Noor et al, 2006), although a pyrenoid was observed in some cells in the latter two studies. The most elongated strain is Dn32EHU (L/W 1.38), which shows a thecal surface with scarce pores without a clear radiating pattern.…”
Section: Taxonomic Remarkssupporting
confidence: 63%
“…Our strain lacks poroids and fits P. rhathymum for most morphological features. Cell dimensions are slightly larger than in the original description by Loeblich et al (1979) and the reports of Mohammad-Noor et al (2006) and Aligizaki et al (2009), but fit well with those given by Fukuyo (1981). The intercalary band of P. rhathymum is described as horizontally striated in Aligizaki et al (2009) and as smooth in Mohammad-Noor et al (2006), while both horizontal and transverse striations have been observed in this study.…”
Section: Taxonomic Remarkssupporting
confidence: 39%
See 3 more Smart Citations